Inhibitory effects of caffeine on gustatory plasticity in the nematode Caenorhabditis elegans. Issue 10 (2nd October 2016) - Urushihata, Takuya; Takuwa, Hiroyuki; Higuchi, Yukako; Sakata, Kazumi; Wakabayashi, Tokumitsu; Nishino, Asuka; Matsuura, Tetsuya
Abstract: The effects of caffeine on salt chemotaxis learning were investigated using the nematode Caenorhabditis elegans . To estimate the degree of salt chemotaxis learning, nematodes were placed in a mixed solution of NaCl and caffeine, and then the chemotaxis index of NaCl was obtained from the nematodes placed on agar medium after pre-exposure to caffeine concentrations of 0.01, 0.1, 0.3, and 1.0%. Locomotor activity and preference behavior for caffeine were also estimated under these caffeine conditions. Nematodes pre-exposed to 0.3% caffeine showed inhibition of salt chemotaxis learning. Additional experiments indicated that nematodes showed a preference response to the middle concentration of caffeine (0.1%), with preference behavior declining in the 0.3% caffeine condition. Stable locomotor activity was observed under 0.01–0.3% caffeine conditions. These results suggest that salt chemotaxis learning with 0.3% caffeine is useful for investigating the effects of caffeine on learning in nematodes. Graphical abstract: : We developed the nematode as a model animal for studying the effects of caffeine on learning. Nematodes pre-exposed to 0.3% caffeine showed inhibition of learning.